Human Resource Practices and Job Satisfaction: Underlying Mechanism of Self Perceived English Ability, Motivation and Chinese Traditionality - Rahman, Mohammad Mahfuzur; Kang, Hwa Shaw (2017)
Objective: Although international management literature has emphasized the value of human resource (HR) practices into the internationalization process, the mechanism in whereby HR practices impact towards employee’s cognitive abilities and motivation is relatively unknown from emerging economies multinationals. This paper examines the association between HR practices that promote learning a foreign language and employees’ self-perceived language ability and motivation to use English in the workplace and how these affects towards overall job satisfaction with Chinese Multinational Enterprises (CMNEs) employees. Methodology: We tested our conceptual model using survey data from 180 CMNEs employees. Results: The results show: (1) HR practices which support developing skills such as English will enhance selfperceived English ability and employee’s motivation to use English in the work place (2) which subsequently has positive behavioural outcomes such as job satisfaction, and (3) Chinese traditionality is a strong moderator between the relationship of HR practices and job satisfaction. Implication: This paper offers new perspectives by advancing the discourse within the field of international management, in the Chinese context.It also presents the managerial implications and recommendations for future research.